2007
DOI: 10.1590/s1516-35982007000600014
|View full text |Cite
|
Sign up to set email alerts
|

Exigências de triptofano e padrão de recuperação do desempenho de poedeiras comerciais após alimentação com rações deficientes em triptofano

Abstract: Este experimento foi conduzido para avaliar as exigências de triptofano e o padrão de recuperação do desempenho de poedeiras alimentadas com rações deficientes em triptofano. Foram utilizadas 160 poedeiras comerciais da linhagem Hisex White distribuídas em um delineamento inteiramente casualizado com cinco níveis de triptofano nas dietas (0,13; 0,15; 0,17; 0,19 e 0,21%), com oito repetições de quatro aves. As poedeiras permaneceram por duas semanas em adaptação (51 a 52 semanas), por seis semanas para avaliaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Similar responses were reported by Deponti et al (2007), who found no effect on feed intake and feed efficiency with increased levels of tryptophan (0.13 to 0.21) for laying hen diets. The authors concluded that the lowest level (0.13%) was not low enough to suppress feed intake.…”
Section: Resultssupporting
confidence: 87%
“…Similar responses were reported by Deponti et al (2007), who found no effect on feed intake and feed efficiency with increased levels of tryptophan (0.13 to 0.21) for laying hen diets. The authors concluded that the lowest level (0.13%) was not low enough to suppress feed intake.…”
Section: Resultssupporting
confidence: 87%
“…Tryptophan is considered the third limiting amino acid in diets based on corn and soybean meal for laying hens (Russell & Harms, 1999;Harms & Russell, 2000;Peganova et al, 2003;Deponti et al, 2007). However, few studies have been conducted to determine the requirement of digestible tryptophan and especially its ideal ratio with digestible lysine in diets for laying hens.…”
Section: Introductionmentioning
confidence: 99%